Evaluation of the Impact of Optical Coherence Tomography on Pediatrician Otologic Examination Judgment - Malinda S. Teague; Ryan M. Nolan (OTO Open, 2023)
Abstract Accurate diagnosis of otitis media is imperative to judicious antibiotic prescription. Visualization of the tympanic membrane and accurate identification of middle ear effusion with standard otoscopy is inherently challenging in pediatrics, especially in the youngest children who are most at risk for otitis media. With the average diagnostic accuracy among primary care physicians of 50% and accurate identification of normal tympanic membrane versus acute otitis media versus otitis media with effusion ranging from 30% to 84% among pediatricians, there is great opportunity for diagnostic improvement and decreasing unnecessary antibiotic use. In a 96‐pediatrician‐blinded otoscopy diagnosis quiz, addition of optical coherence tomography, a novel depth‐imaging technology, resulted in a 32% improvement in fluid identification, and 21% increase in diagnostic accuracy. This study suggests that the clinical use of this technology promises to improve diagnostic accuracy and antibiotic stewardship in pediatrics.